Novel Susah Sinyal Karya Ika Natassa dan Ernest Prakasa: Kajian Stilistika - M Fatkhur Rohman; Maria Matildis Banda; I Nyoman Weda Kusuma (Udayana University, 2022)
This study aims to determine the description of the structure (plot, setting, character) and style of language, namely the novel